Peripheral motor nerve function in diabetic autonomic neuropathy. Issue 5 (May 1976) - Ewing, D J; Burt, A A; Williams, I R; Campbell, I W; Clarke, B F
Abstract : Motor conduction velocity was measured in the median, ulnar and common peroneal nerves of 32 diabetics with clinical features of autonomic neuropathy. The responses to the Valsalva manoeuvre and sustained handgrip, and the postural fall in blood pressure were used to assess the integrity of the autonomic nervous system. Abnormalities in the three autonomic function tests were significantly correlated with the forearm conduction velocity of the ulnar nerve, the conduction velocity and motor latency of the common peroneal nerve, and the H reflex. These results show that, in diabetics with autonomic neuropathy, abnormalities in the autonomic nervous system parallel changes in the peripheral nerves. Any diabetic with peripheral neuropathy should be examined for evidence of autonomic nervous system involvement.